(untitled) (Philological Studies, 2019)
The aim of this paper is to present parallels between a northeastern Macedonian dialect (Ovche Pole dialect) and a northeastern Slovenian dialect (Slovenian-gorishki – gorichanski dialect). In this respect we will focus primarily on the changes that occur on phonetic-phonological, morphological, lexical and wordformation level in the Ovche Pole dialect, i.e. the language of Crn and Gugj; and on lexical and word-formation level in the Slovenian-gorishki – gorichanski dialect. The rich dialectological material collected in the field indicates that these two dialects are both related and distinct, even though they belong to the South Slavic linguistic world.